PKC-theta-mediated signal delivery from the TCR/CD28 surface receptors - Isakov, Noah; Altman, Amnon (Frontiers in Immunology, 2012)
Protein kinase C-theta (PKCθ) is a key enzyme in T lymphocytes, where it plays an important role in signal transduction downstream of the activated TCR and the CD28 costimulatory receptor. TCR/CD28 engagement triggers the translocation of the cytosolic PKCθ to the plasma membrane, where it localizes at the center of the immunological synapse (IS), which forms at the contact site between an antigen-specific T cell and antigen-presenting cells (APC). The cellular redistribution of PKCθ in resting versus activated T cells has been thoroughly investigated, but the mechanisms governing its translocation to the center of the IS, and how this unique localization relates to the biological activity of PKCθ have remained unclear until recently. A very recent study has shown that the unique V3 (hinge) domain of PKCθ is essential and sufficient for its localization at the IS, where it is anchored to the cytoplasmic tail of CD28 via an indirect mechanism, involving the Lck as an intermediate. Furthermore, the PKCθ-CD28 complex, which forms upon antigen stimulation, is localized at a newly recognized, TCRlow subregion of the central IS, where it forms an outer ring around the very center, TCRhigh subregion. Importantly, the association of PKCθ with CD28 is also essential for PKCθ-mediated activation of downstream signaling pathways, including the transcription factors NF-κB and NF-AT, which are sine qua non for the productive activation of T lymphocytes. Indeed, the use of V3-altered PKCθ mutants or the isolated V3 domain as a negative dominant mutant demonstrated that strategies, which disrupt the interaction between PKCθ and CD28, block T cell activation, proliferation and differentiation into pathogenic Th2 and Th17 (but not Th1) effector helper T cells. The recent progress made in understanding of the mechanism of recruitment and regulation of PKCθ activity at the IS is likely to facilitate the development of PKCθ-based therapeutic modalities for T cell-mediated diseases.